Circulating microRNA-196a/b are novel biomarkers associated with metastatic gastric cancer. (September 2016) - Tsai, Ming-Ming; Wang, Chia-Siu; Tsai, Chung-Ying; Huang, Chung-Guei; Lee, Kam-Fai; Huang, Hsiang-Wei; Lin, Yang-Hsiang; Chi, Hsiang-Cheng; Kuo, Liang-Mou; Lu, Pei-Hsuan; Lin, Kwang-Huei
Abstract: miR-196a and/or miR-196b, involved in cancer initiation and progression, are frequently upregulated in tumour tissues. However, the clinical significance of these microRNAs in gastric cancer (GC) remains to be clarified. In the current study, we investigated the potential utility of circulating miR-196a/b as novel biomarkers for early detection and/or metastatic prognosis of GC. The quantitative real time-polymerase chain reaction data revealed markedly higher pre-operative circulating miR-196a and miR-196b levels in GC patients than healthy controls. Receiver-operating characteristics curve analysis showed that circulating miR-196a, miR-196b and combined miR-196a and miR-196b (miR-196a/b) are more effective than carcinoembryonic antigen or carbohydrate antigen 19-9 alone in distinguishing GC patients from healthy controls, with higher sensitivity and specificity. Circulating miR-196a exhibited higher diagnostic capacity than combined miR-196a/b or miR-196b alone, highlighting its potential as an effective plasma biomarker for GC. In clinicopathological analysis, elevated circulating miR-196a/b levels were highly correlated with metastatic potential or more advanced stages of disease and poorer survival. In addition, the expression levels of circulating miR-196a/b were reduced after surgical resection in GC patients. Taken together, we propose that circulating miR-196a/b serve as a more sensitive and specific novel biomarker than carbohydrate antigen 19-9 for GC monitor, diagnosis and prognosis. Highlights: The circulating miR-196a/-196b are more sensitive or specific than carcinoembryonic antigen or carbohydrate antigen 19-9 alone. The elevated circulating miR-196a/-196b levels are highly correlated with metastatic potential and poorer survival. The circulating miR-196a/-196b serve as novel biomarkers for gastric cancer diagnosis and prognosis.